Front Cover: Cosolvent and Crowding Effects on the Temperature‐ and Pressure‐Dependent Dissociation Process of the α/β‐Tubulin Heterodimer (ChemPhysChem 9/2019). Issue 9 (18th April 2019) - Schummel, Paul Hendrik; Anders, Christian; Jaworek, Michel W.; Winter, Roland
Abstract : The Front Cover illustrates that by adjusting the level of natural co‐solutes like TMAO, the deteriorating effect of deep‐sea hydrostatic pressures on tubulin association can be suppressed. More information can be found in the Article onpage 1098 in Issue 9, 2019 by P. H. Schummel et al (DOI:10.1002/cphc.201900115 ).